EFEKTIFITAS MEDIA E-COMIC TERHADAP KESADARAN KEWARGANEGARAAN SISWA SEKOLAH DASAR - Dwiaryani, Mirna; Tyas, Firda Anggraini Prasetyaning; Larasati, Natasha; Fidelia, Felisiana; Hidayah, Eva Nur (Program Studi PPKn Universitas Pendidikan Ganesha, 2025)
This study aims to develop E-comic learning media as a solution to increase student motivation, attention, and understanding in Pancasila Education learning in elementary schools. The problems found are low focus, lack of interest, and passive attitudes of students when learning only uses the lecture method. The study used qualitative methods through observation, interviews with teachers, and literature studies. The results of the study show that students are more interested in interactive visual media, and teachers assess that E-comics can help simplify abstract material to make it easier to understand. The implementation of E-comics was considered effective in increasing learning engagement, reducing boredom, and supporting the contextual delivery of Pancasila values. It can be concluded that E-comics are a relevant and useful medium for improving the quality of Pancasila Education learning. This study recommends the use of E-comics as a supporting medium in learning and training for teachers to develop attractive visual media.